Intellectual Capital and Maqashid Sharia Performance of Islamic Banking In Indonesia - Widyantono Arif (www.amertainstitute.com, 2023)
The research aim to analyze the effect of intellectual capital indicators on the performance of Islamic banks from 2016 to 2019 year. The iB-VAIC method for intellectual capital is measured based on working capital, human capital, structural capital, while bank performance variables are measured using the maqashid sharia approach developed by Mohammed et al based on Abu Zahra's maqashid sharia concept, using secondary data from audited financial reports and annual reports for 14 Islamic commercial banks in Indonesia were collected using documentation and analyzed using multiple regression analysis. These results indicate that human capital as a proxy for intellectual capital has a positive effect on the performance of maqashid sharia. This research failed to show the effect of capital employed and structural capital on the maqashid sharia performance.